Numerical Study of Damage to Rock Surrounding an Underground Coal Roadway Excavation. (10th September 2020) - Wei, Jiangbo; Wang, Shuangming; Zhao, Zhou; Li, Delu; Guo, Lipeng
Abstract : In coal mines, underground roadways are required to transport coal and personnel. Such tunnels can become unstable and hazardous. This study simulates deformation and damage in the rock surrounding a shallow coal seam roadway using particle flow code. A numerical model of particle flow in the surrounding rock was constructed based on field survey and drilling data. Microcharacteristic indices, including stress, displacement, and microcrack fields, were used to study deformation and damage characteristics and mechanisms in the surrounding rocks. The results show that the stress within the rock changed gradually from a vertical stress to a circumferential stress pattern. Stress release led to self-stabilizing diamond-shaped and X-shaped tensile stress distribution patterns after the excavation of the roadway. Cracking increased and eventually formed cut-through cracks as the concentrated stress transferred to greater depths at the sides, forming shear and triangular-shaped failure regions. Overall, the roof and floor were relatively stable, whereas the sidewalls gradually failed. These results provide a reference for the control of rock surrounding roadways in coal mines.